Application of a controlled outside cold airflow by a PID controller to improve the performance of a household refrigerator - Emna Aridhi; Mehdi Abbes; Abdelkader Mami (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The present paper aims to prove the efficiency of using the cold to improve the performance of a household refrigerator. It is produced naturally in countries that are characterized by a severe wintry climate. The cold airflow is spread out inside a cavity covering the side wall of the appliance, which is connected to the inlet and outlet ducts. For that purpose, a Simulink model is proposed to model this installation. The internal air temperature is computed according to the evaporator temperature and the outside cold airflow that is also computed according to the outside temperature and controlled by a PID controller. The simulation results show that when the internal air temperature is higher than the desired one and the outside temperature is low enough, the controlled cold airflow used as a second cooling source allowed to speed-up the cooling inside the refrigerator compartment of about 36.21% and to reach an energy saving of about 36.23% compared with the classical thermostatic control.